2016
DOI: 10.1016/j.tetlet.2016.03.041
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Nd/Na heterogeneous catalyst from bench-stable and inexpensive Nd salt for an anti-selective catalytic asymmetric nitroaldol reaction

Abstract: A Nd/Na heterobimetallic complex prepared from an amide-based chiral ligand, Nd alkoxide, and NaHMDS is a highly efficient heterogeneous catalyst for an anti-selective catalytic asymmetric nitroaldol reaction. Nd alkoxide is sensitive to moisture, expensive, and scarce, making it difficult to use the Nd/Na catalyst in large-scale applications. Herein we describe a new protocol that allows for catalyst preparation from bench-stable and inexpensive NdCl 3 •6H 2 O with comparable catalytic activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 52 publications
0
15
0
Order By: Relevance
“…Hence, with the help of the flow reactor system they were able to run the continuous synthesis during 28 h producing 12.4 g of the intermediate 58 , a key intermediate for a therapeutic candidate drug for the treatment of chronic obstructive pulmonary disease, with high stereoselectivity ( anti / syn 93/7, 92 % ee) and a turnover number of 200 (Scheme b). Later on, the same authors reported the use of the less expensive NdCl 3 ⋅ 6H 2 O and NaO t Bu instead of NdO 1/5 (O i Pr) 13/5 and NaHMDS for preparing a catalyst that showed identical catalytic activity that could be used for large‐scale applications . Finally, Shibasaki extended its confinement strategy for preparing other self‐assembling catalysts using based ligand 59 and Er(O i Pr) 3 (Scheme c) .…”
Section: Carbon Nanotubes‐based Catalystsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, with the help of the flow reactor system they were able to run the continuous synthesis during 28 h producing 12.4 g of the intermediate 58 , a key intermediate for a therapeutic candidate drug for the treatment of chronic obstructive pulmonary disease, with high stereoselectivity ( anti / syn 93/7, 92 % ee) and a turnover number of 200 (Scheme b). Later on, the same authors reported the use of the less expensive NdCl 3 ⋅ 6H 2 O and NaO t Bu instead of NdO 1/5 (O i Pr) 13/5 and NaHMDS for preparing a catalyst that showed identical catalytic activity that could be used for large‐scale applications . Finally, Shibasaki extended its confinement strategy for preparing other self‐assembling catalysts using based ligand 59 and Er(O i Pr) 3 (Scheme c) .…”
Section: Carbon Nanotubes‐based Catalystsmentioning
confidence: 99%
“…[52] Hence, with the help of the flow reactor system they were able to run the continuous synthesis during 28 h producing 12 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 (O i Pr) 13/5 and NaHMDS for preparing a catalyst that showed identical catalytic activity that could be used for large-scale applications. [53] Finally, Shibasaki extended its confinement strategy for preparing other self-assembling catalysts using based ligand 59 and Er(O i Pr) 3 (Scheme 21c). [54] The novel hybrid MWCNT-confined catalytic material 60 resulted a good catalyst at 5 mol % for the Mannich-type reaction between a-cyanoketone 61 and N-Boc-imine 62 in a continuous-flow apparatus able to deliver 6.27 g of the corresponding Mannich-adduct 63 after 56 h with a high stereoselectivity (syn/anti 93/7, 94 % ee; Scheme 21d).…”
Section: Supramolecular Functionalizationmentioning
confidence: 99%
“…In a laboratory scale reaction, an asymmetric nitroaldol reaction of nitroethane 31 in a continuous‐flow platform was demonstrated at over 10‐g scale with a turnover number of 200, producing 32 with high stereoselectivity as a key intermediate for a therapeutic candidate (Scheme b) . NdO 1/5 (O i Pr) 13/5 and NaHMDS could be replaced by the much less expensive NdCl 3 ⋅ 6H 2 O and NaO t Bu for catalyst preparation . The catalyst obtained from this new procedure exhibited identical catalytic activity, suggesting its potential for large‐scale application.…”
Section: Noncovalent Immobilization Of Active Catalysts Onto Cntsmentioning
confidence: 99%
“…Although alkyl groups Scheme 30. Ytterbium-catalyzed nitroaldol reaction of aldehydes with nitromethane [52]. on the 3-position (R 1 ) of the 2H-azirine were compatible, the substrate having a methyl group (R 1 = Me, R 2 = Ph) provided a low enantioselectivity (30% ee).…”
Section: Enantioselective Lanthanide-catalyzed 12-nucleophilic Additmentioning
confidence: 99%
“…Indeed, this Nd alkoxide is expensive, instable to moisture, and requires handling in a glove box under an inert atmosphere, which hampers its widespread use. To encounter this problem, a novel protocol was described that allowed for catalyst preparation from bench-stable and inexpensive NdCl 3 (6H 2 O) with comparable activity [52]. As shown in Scheme 29, when the asymmetric nitroaldol reaction of aldehydes 77a,i-k,n-r with Scheme 21.…”
Section: Nitroaldol Reactionsmentioning
confidence: 99%